2012
DOI: 10.1103/physrevd.85.114016
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid model for QCD deconfining phase boundary

Abstract: Intensive search for a proper and realistic equations of state (EOS) is still continued for studying the phase diagram existing between quark gluon plasma (QGP) and hadron gas (HG) phases.Lattice calculations provide such EOS for the strongly interacting matter at finite temperature (T ) and vanishing baryon chemical potential (µ B ). These calculations are of limited use at finite µ B due to the appearance of notorious sign problem. In the recent past, we had constructed a hybrid model description for the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 85 publications
(123 reference statements)
2
31
0
Order By: Relevance
“…We have used the quasiparticle description to define the basic properties of QGP since earlier we have shown that quasiparticle description provides the proper and realistic thermodynamical and transport behaviour of QGP phase [23,24]. We want to provide the correct temperature dependence of σ el since it is not yet established.…”
Section: Introductionmentioning
confidence: 99%
“…We have used the quasiparticle description to define the basic properties of QGP since earlier we have shown that quasiparticle description provides the proper and realistic thermodynamical and transport behaviour of QGP phase [23,24]. We want to provide the correct temperature dependence of σ el since it is not yet established.…”
Section: Introductionmentioning
confidence: 99%
“…1(a)). Such valley-dependent Berry curvature gives rise to intriguing phenomena [10,11] such as the valley optical selection rule [12][13][14], the valley Zeeman effect [15][16][17][18] and the valley Hall effect [19][20][21]. Further manipulation of electrically induced valley magnetization has been demonstrated by lowering the crystal symmetries of TMDs by strain [21], but the dependence on strain yet remains unclear.…”
mentioning
confidence: 99%
“…[30,[38][39][40]. Several attempts have also been made to study the EOS for interacting QCD matter [31,32,34,36,41,42]. For example, new lattice results for the equation of state of QCD with 2 + 1 dynamical flavors were obtained in [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [36] deals with hybrid model in constructing a deconfining phase boundary between the hadron gas and the QGP and provides a realistic EOS for the strongly interacting matter. Furthermore, in [31,32] the author have studied the thermodynamic properties of weakly interacting unpolarized QGP matter by using a MIT bag model within one gluon exchange (OGE) interaction.…”
Section: Introductionmentioning
confidence: 99%